Dairy cow performance is associated with longitudinal microRNA profiles - Madison MacLeay; Francesc Xavier Donadeu; Georgios Banos (PLoS ONE, 2025)
Modern high producing dairy cows are still affected by poor fertility and disease, despite improvements achieved through genetic selection programs. Additional biomarkers of health and performance traits in cattle could enhance animal welfare and profitability by allowing farmers to cull animals before problems occur. We performed pilot investigations of plasma microRNA (miRNA) profiles during early life as potential biomarkers associated with future performance in dairy cows. The latter included survival to two years of age, age at first calving, yield of milk, fat and protein, mastitis and lameness traits, conception rate, number of services per conception, and calving interval. Using qPCR, we obtained longitudinal measurements and ratios involving nine miRNAs (miR-126-3p, miR-127, miR-142-5p, miR-154b, miR-27b, miR-30c-5p, miR-34a, miR-363, miR-425-3p) in plasma samples from three age groups: calves (<1 month), heifers (14–23 months), and first lactation cows (29–35 months). Changes in miR-126-3p from calf to first lactation cow were associated with first lactation milk yield and second lactation milk somatic cell count (an udder health indicator). Moreover, the miR-127 to miR-30c-5p ratio in cows was associated with milk fat and protein yield in the first two lactations, whereas miR-142-5p levels and several miRNA ratios involving this miRNA, were associated with second calving interval (a cow fertility trait). Our results identified novel early life biomarkers that warrant further investigation to determine whether they may predict dairy cattle performance.